Developing very short computerised early vocabulary assessments in a multilingual setting - Chai, Jun Ho (2022)
The MacArthur-Bates Communicative Development Inventories (CDIs) are one of the most widely adapted sets of parent-report instruments for assessing young children’s early vocabulary acquisition (Fenson et al., 2007; Frank, Braginsky, Marchman, & Yurovsky, 2021). The MacArthur-Bates Communicative Development Inventories (CDIs) are valid and reliable not only with children who are developing typically (Fenson et al., 2007, 1993; Pan, Rowe, Spier, & Tamis-Lemonda, 2004; Rescorla, Ratner, Jusczyk, & Jusczyk, 2005; Law & Roy, 2008), but also with children developing atypically (Galeote, Checa, Sánchez- Palacios, Sebastián, & Soto, 2016; Luyster, Lopez, & Lord, 2007; Mayne, Yoshinaga-Itano, Sedey, & Carey, 1998; Mayne, Yoshinaga-Itano, & Sedey, 1999; D. Thal, DesJardin, & Eisenberg, 2007). The CDIs provide extensive insights into children’s vocabulary sizes, yet they rely on parents’ knowledge of their children. Furthermore, the completion of each CDI is time-consuming as the parent has to assess their child’s word knowledge item-by-item, often amounting to 600 words or more. Although previous efforts were made to develop 100-item short-form versions, it is time-consuming to develop short-forms for each language, and their administrations remain a considerable time investment for parents when completing such forms. The process of completing CDIs is made even more laborious, when having to fill out CDIs for several languages, for children exposed to more than one language, such as most children from Malaysia, a linguistically diverse country, where bi- and multilingually-exposed children constitute a significant proportion of the population.